Pengaruh Likuiditas, Profitabilitas, Struktur Modal dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan pada Sektor Energi yang Terdaftar di Bursa Efek Indonesia - Nahendra; Safitri, Ervita; Kalsum, Ummi (PT Maju Malaqbi Makkarana, 2025)
This study aims to test and analyze the effect of Liquidity, Profitability, Capital Structure and Company Growth on Company Value in the energy sector listed on the Indonesian Stock Exchange. The type of research used is quantitative and uses secondary data types. The population in this study was 19 companies with a total of 16 samples for 5 years, namely 80 data samples selected using purposive sampling. The results of this study indicate that liquidity, profitability, capital structure and company growth have a significant effect on company value. Liquidity and capital structure have a significant effect on company value, Profitability and company growth do not affect company value with an Adjusted R Square value of 8.10%. While explained by other factors.